Drying models and desiccation tolerance of Tectona grandis L.f. and Gmelina arborea Roxb. Seeds - Correa Alvarez, Ender Manuel; Alvarez A., Slim Camilo; Espitia C., Miguel Mariano; Cardona A., Carlos Enrique (Revista de Ciencias Agrícolas, 2014)
Seed drying is very important in the conservation process of forest genetic resources, it implies the reduction of humidity content (HC) to the recommended levels by utilizing techniques that do not deteriorate its viability and contribute to the preservation of its physiological quality during storage. The object of this study was to estimate regression models to predict seed drying time with silica gel, as well as evaluate desiccation effects on the physiological quality of Tectona grandis L.f and Gmelia arborea Roxb seeds. Silica gel proportions were evaluated in terms of seed weight 1:1; 1.5:1; 2:1; 2.5:1, and 3:1 every 24 hours during 10 days, while monitoring the HC of the seeds. For every silica gel proportion, regression equation selection was based on the variation coefficient (VC), determination coefficient (R2), and mean squares of error (MSE). The equations were validated and subsequently used to determine the drying time required for obtaining a HC between 3% and 6.5%; furthermore, they were useful as a basis to determine desiccation tolerance. The use of silica gel allowed average desiccation percentages greater than 62% of the initial HC. Furthermore, highly significant equations (P < 0.01) with good adjustment (R2 =0.94) were obtained, and germination parameters did not show detriment with the drying treatments, confirming the orthodox condition of these seeds.